Pengaruh Quick Ratio (QR) dan Current Ratio (CR) Terhadap Net Profit Margin (NPM) pada Pt. Jasa Marga Tbk (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Quick Ratio (QR) and Current Ratio (CR) on Net Profit Margin (NPM) at PT. Jasa Marga Tbk. The research employed an associative quantitative approach using secondary data derived from the company's financial statements for the period 2015–2024. Data analysis was conducted using multiple linear regression, supported by classical assumption tests, correlation analysis, coefficient of determination, and hypothesis testing. The results indicate that Quick Ratio (QR) has a positive and significant effect on Net Profit Margin (NPM), while Current Ratio (CR) does not have a significant effect on Net Profit Margin (NPM). Simultaneously, Quick Ratio (QR) and Current Ratio (CR) significantly affect Net Profit Margin (NPM). The coefficient of determination shows that 51.7% of the variation in Net Profit Margin can be explained by the two independent variables, while the remaining 48.3% is influenced by other factors outside the research model. These findings suggest that effective liquidity management, particularly through maintaining an optimal Quick Ratio, can contribute to improving corporate profitability.